Effects of Mixing and Stratification on the Vertical Distribution and Size Spectrum of Zooplankton on the Shelf and Slope of the Northern South China Sea - Chen, Kaixuan; Zhou, Meng; Zhong, Yisen; Waniek, Joanna J.; Shan, Congwen; Zhang, Zhaoru (Frontiers in Marine Science, 2022)
The northern shelf and off-shelf regions of the South China Sea (SCS) present a stark contrast between being eutrophic from terrestrial runoffs of nutrients and biota and being oligotrophic with multiple nutrient limitations due to the distance to land sources and stable permanent stratification. The abundance, size and trophic structures of plankton in the shelf and off-shelf regions were studied in a joint Sino-German cruise conducted between September 1 and 24 2018. A Laser Optical Plankton Counter was mounted on a water sampler-CTD (conductivity-temperature-depth) system for studying the horizontal and vertical distributions of plankton structures in a size range between 0.1 and 35 mm and their relationships with hydrographic and biological features in the northern SCS and its shelf region. Results revealed the subsurface chlorophyll maximum layer (SCM) below the pycnocline, and plankton aggregation near the SCM about the depth of 50-60 m. The distributions of small plankton between 0.1 and 0.5 mm were stronger correlated with stratification and SCM than those of large plankton. Analyzing the intercept and slope of a normalized biovolume spectrum (NBVS) as an indicator for abundance and size structure of a plankton community, results revealed that in the shelf region the slopes exhibited no significant vertical variations in the water column regardless stratification and SCM. In contrast, in the off-shelf stratified water column the intercepts and slopes were lower and flatter in the surface layer, higher and steeper in SCM layer, and the lowest and flattest in the deep layer. Stirring by the typhoon also altered both the abundances and size structures of the plankton communities, with significant regional differences. This study elucidates the variances of plankton abundances, distributions, NBVS slopes and intercepts among different water column structures in both shelf and off-shelf regions of the northern SCS.